Subsurface Fault Mapping of Central Luconia Province, Offshore Sarawak through Airborne Full Tensor Gradiometry (Air-FTGÂ®) Interpretation - Jamaludin, S.N.F. (Slovnaft VURUP a.s, 2021)
This study aims to delineate different structural trends at different depth ranges in Central Luconia, offshore Sarawak by utilizing the depth (Z) component from the airborne gravity. Different wavelengths range applied on the gravity data allows estimation of different depth in the subsurface, thus providing tools for detailed fault mapping in this area. Very short wavelength data include Contact Lineament Processed data at 5-20 km yield NE-SW oriented faults that stand-alone from the other gravity anomalies maps interpreted. This is assumed to be related to recent gravitational tectonic that impacted this area. Short wavelength Tzz to intermediate wavelength Txz and Tyz, as well as long wavelength CLP data possesses dominant NW-SE trend. It is interpreted to follow the major NW-SE orientation of West Baram and West Balingian Lines that bounded Central Luconia. An E-W orientation is detected in the deep subsurface (long wavelength) and has possibility to reflect the orientation of the basement. Comparison of gravity anomaly with existing location of carbonate build-ups reveal most of carbonate in Central Luconia grow in low gravity areas and exhibit smaller size build-ups compared to the build-ups in West Luconia that have bigger size and grow on high positive gravity areas. An obvious circular structure with low gravity response in Central Luconia is further evaluated with existing exploration wells nearby and it is suggested for further evaluation for potential hydrocarbon exploration area in Central Luconia. Â© 2021, Petroleum and Coal. All rights reserved.